509 Ranking of cardiovascular risk factors in Romania‐ regional epidemiological approach (Balneo and PRM Research Journal, 2024)
Abstract: An extensive epidemiological investigation was applied regarding the riskfactors, to a cohort of patients with pre‐existing heart disease, hospitalized for tertiaryprophylaxis in a rehabilitation hospital. The group of 499 patients from all regions of thecountry respected the proportions of gender and environment of origin for the generalpopulation of Romania and was adjusted according to regional proportions.The ranking of risk factors and protection factors present in the studied population wasmade, at the level of each of the 8 regions of the country and for the whole countryconsolidated. The profile of the cardiovascular patient was identified. We used risk factorsfor population characterization, not for aggregation into tools for assessing totalcardiovascular risk (as is the trend in large cohort studies since Framingham)The data processing was done to be able to develop prevention strategies in the interestof the specific individual, not to standardize population characteristics and translate themto the individual thus decreasing their appropriateness.Keywords: 1 cardiovascular risk‐factors, 2 cardiovascular diseases prevention , 3 cardiovascularrehabilita‐tion